2021
DOI: 10.3390/app112311465
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the Motion and Interaction of a Droplet of an Inkjet Printing Process with Physically Treated Polymers Substrates

Abstract: This study examines the effect of energetic surface treatment on the adhesion strength of high-density polyethylene (HDPE), polypropylene (PP) and polyethylene terephthalate (PET) substrates. The purpose of this work is to determine the surface wettability of polymers suitable for food contact. These plastics have been treated with various pre-treatment methods to improve surface tension and good adhesion for inkjet printing and avoid any visual changes. It is important to determine the adhesion of the ink to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…The change in SFE of the treated surface affects the ink droplet shape and its diameter, which can develop in time. This effect is more pronounced for LTP-treated substrates [ 18 ]. Moreover, these authors observed that the UV–ink could undergo considerable degradation of its adhesion after 24 h on untreated and cleaned surfaces compared to stable ink adhesion to LTP-treated surfaces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The change in SFE of the treated surface affects the ink droplet shape and its diameter, which can develop in time. This effect is more pronounced for LTP-treated substrates [ 18 ]. Moreover, these authors observed that the UV–ink could undergo considerable degradation of its adhesion after 24 h on untreated and cleaned surfaces compared to stable ink adhesion to LTP-treated surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the DCSBD plasma modified the surface of polymethylmethacrylate (PMMA) and polycarbonate (PC) substrates, often considered glass substitutes in UV–digital printing. The end-user of UV–digital printers requires a substantial increase in the adhesion and standardization of the printed layer quality on polymer substrates from different manufacturers [ 18 ]. Thus, process variables (plasma reactor configuration, treatment time, and treatment distance) were identified and used for experimental tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of such printing depends on the choice of substrate materials and the printed color pattern. Commonly used polymeric materials have a smooth surface and low surface energy, which often (but not inevitably) causes an insufficient adhesion of inks used for UV-digital printing [15][16][17][18]. The adhesion of the printed color pattern, or its abrasion resistance, then affects the final product's usage and positioning, or the printed substrate's impact, depending on climatic conditions (e.g., outdoor conditions, humidity, and temperature).…”
Section: Introductionmentioning
confidence: 99%
“…Single droplet splitting is vital for the highly efficient clinical detection [24], precious inkjet printing [25], open-air microfluidic devices [26], and interfacial heat transfer [27], whereas finding an efficient and quick method of separating a drop with little assistance from tools is still challenging. Recently, superhydrophobic surfaces have been shown to be a resourceful way to control wettability and manipulation of droplet motions.…”
Section: Introductionmentioning
confidence: 99%